Treibhaus : 31 Künstler in Düsseldorf. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1981)
Adler, Jaroslav ; Bunk, Holger ; Christian, Abraham David ; Dobloug, Jorgen ; Ecker, Bogomir ; Edler, Dorit ; Gläsker, Horst ; Jaworski, Halina ; Jung, Klaus ; Knöller, Paco R. ; Kunc, Milan ; Lista, Monica ; Loock, Ulrich ; Luy, Wolfgang ; Meuser, Klaus ; Meyer, Jürgen ; Minarik, Ladislav ; Moustakidis, Soulis ; Münch, Horst ; Nattermüller, Ulrike ; Reichelt, Moritz ; etc.
Treibhaus : 31 Künstler in Düsseldorf, Kunstmuseum Düsseldorf, 31.5. bis 28.6.1981
boek